Handbook of research on transmedia storytelling, audience engagement, and business strategies - Hernández-Santaolalla, Víctor; Barrientos Bueno, Mónica (Advances in business strategy and competitive advantage., 2020)
"This book provides theoretical, reflective, and empirical perspectives on transmedia storytelling and digital marketing strategies in relation to audience engagement"--